Serotype and Clinical Performance of Dengue Virus Infection on the Year 2009 - Soegijanto, Soegeng; Darmowandowo, Widodo; Ginting, Amor Peraten; Yamanaka, Atsushi (Indonesian Journal of Tropical and Infectious Disease, 2010)
Dengue hemorrhagic fever is one of the important health problem in Indonesia, mortality rate is becoming decrease but many dengue shock syndrome cases is very difficult to be help. Previous study showed that some of DEN 2 and DEN 3 virus cases could show a clinical performance of severe dengue virus infection such as dengue shock syndrome. There are four serotype of dengue virus infection can cause primary and secondary infection. The aim of this research is to know the relationship between clinical performance of dengue virus infection and serotype dengue virus and also to know the role of primary and secondary infection and age of dengue virus cases. A prospective analytic observational study, which was conducted in Dr. Soetomo hospital since January 2009. RT-PCR was used to attempt to identify the infecting serotype from dengue virus isolated using vero cell. Antibody responses were measured by ELISA and clinical manifestation were measured with the WHO criteria 1997. Dengue serotype identification by RT-PCR was 70 patients. Virus types were DEN-2 65(92.8%), DEN-1 3(4.2%), and DEN-3 2(2.8%). Patients with DEN-1 genotype IV were more trend severe disease DSS and unusual infection. Commanly usually secondary exposure cause more severe clinical manifestation than primary exposure (p = 0.035) but in this study found that all of DEN-1 genotype IV, primary or secondary infection to show severe clinical manifestation of dengue virus infection. We can conclude that DEN-2 was the most dominant serotype in Dr. Soetomo Hospital. On Primary and secondary infection, DEN-1 genotype IV showing more severe than DEN-2 and DEN-3.